Caspofungin: a review of its characteristics, activity, and use in intensive care units. Issue 12 (1st December 2020) - Hashemian, Seyed MohammadReza; Farhadi, Tayebeh; Velayati, Ali Akbar
ABSTRACT: Introduction: Candidemia is the fourth frequent reason of healthcare-related bloodstream infections in critically ill patients. For initial management of (suspected) invasive candidiasis in critically ill patients, usage of an echinocandin, e.g. caspofungin, has been recommended. Areas covered: In this study, characteristics of caspofungin and its use in intensive care unit (ICU) patients are reviewed based on an electronic search using PubMed and Google scholar. Expert opinion: Caspofungin is a semisynthetic derivative from pneumocandin B and the first member of the echinocandins that was approved by the U.S. Food and Drug Administration (FDA) to fight fungal infection. Caspofungin inhibits the enzyme β(1, 3)-D-glucan synthase of the fungal cell wall resulted in inhibition of the synthesis of β(1, 3)-D-glucan. For critically ill patients, inter- and intraindividual variations affect the caspofungin concentration. The incidence rates and densities of candidemia in surgical ICUs may be higher than medical ICUs resulting in a higher burden of candidemia in surgical ICUs. However, the mortality rate in surgical ICU patients with candidemia is higher than that medical ICU patients due to differences in their underlying conditions.